Działania naukowe pracowników Biblioteki Uniwersyteckiej w Poznaniu w ostatnich dziesięciu latach (2007–2016) – analiza i efekty - Jazdon, Krystyna; Szulc, Aleksandra (Biblioteka Uniwersytecka w Poznaniu, 2018)
Biblioteka naukowa funkcjonuje w otoczeniu stworzonym przez warunki prawne, statut uczelni, regulaminy oraz misję biblioteki. Organizuje dostępy do wiedzy, podejmuje działania dydaktyczne, promuje naukę. Zapewnia wysokiej jakości obsługę użytkowników, a pracownicy systematycznie podnoszą swoje kwalifikacje zawodowe. Biblioteka Uniwersytecka w Poznaniu współpracuje ze środowiskiem nauki i kultury, aktywnie włącza się w działania wspomagające budowanie społeczeństwa wiedzy.

The article discusses the various information related activities of the University Library in Poznań, as a means of promoting learning and access to knowledge in all spheres of life. Employees of the University Library systematically upgrade their professional qualifications so as to deliver a high quality of user service. The scientific library functions in an environment created by legal conditions, university statutes and other regulations, cooperates with the science and culture environment, and actively participates in varied activities and programmes thus supporting the building of a knowledge society.
Scientific activities of employees of the University Library in Poznań over the last ten years (2007–2016) – analysis and results
Keywords: otoczenie prawne; działania organizacyjne; kadra BU; bibliotekarze dyplomowani; publikacje; konferencje; seminaria; warsztaty; szkolenia; zebrania naukowe; wystawy; granty; projekty badawcze; działania własne; wydawnictwa; popularyzacja nauki; University Library; legal environment; organizational activities; staff; certified librarians; publications; conferences; seminars; workshops; trainings; scientific meetings; exhibitions; grants; research projects; publishing houses; popularization of science